Traumatismo psíquico: realidade dos fatos, realidade psíquica e des(a)tino do sujeito - Santos Filho, Francisco Carlos dos (2011)
This study aims to investigate the effects of psychic traumatism in the subject´s psychic organization and the destinations that the traumatic situation may determine once it is installed in the mental apparatus. It is a study on psychoanalytic clinic, but it is also a review on trauma metapsychology following the theoretical production by some important authors in psychoanalysis. The first chapter presents an examination of the concept of trauma and its evolution throughout Freud´s body of work. The second chapter delineates how two classic authors Ferenczi and Winnicott work with that concept and with its clinical implications. The third chapter examines the thought of three contemporary authors André Green, Jean Laplanche and Silvia Bleichmar concerning metapsychology of trauma and the resources to approach it in the clinic. Clinical materials are presented in each chapter with the aim of illustrating the metapsychological concepts proposed by the authors and of indicating the possibilities of treatment of psychic suffering in trauma situations